Residual stress measurements of lean duplex stainless steel welded sections. (November 2021) - Li, Dongxu; Paradowska, Anna; Uy, Brian; Wang, Jia; Proust, Gwénaëlle; Kazemzadeh Azad, Sina; Huang, Yerong
Abstract: Lean duplex stainless steel (LDSS) has been increasingly utilised in engineering applications due to its excellent durability, corrosion resistance, as well as superior structural and economic benefits. Moreover, compared to cold-form sections, welded members have significant structural advantages, and thus, have been widely used in many engineering practices. However, as one of the key factors affecting the performance of structural components, residual stresses of LDSS welded sections have not been sufficiently investigated. Therefore, square and H-shaped LDSS welded sections were considered in the present experimental programme. Accurate measurements of the tensile and compressive residual stresses were conducted through the non-destructive neutron diffraction method. As LDSS is a dual-phase material, neutron diffraction measurement was repeated twice for each specimen to obtain the individual phase residual stresses (ferrite-phase, α and austenite-phase, γ ). Hardness analysis, as well as microstructural characterisation using optical microscopy and electron backscatter diffraction (EBSD) were thereafter performed to ascertain the volume fraction of each phase, based on which the residual stresses along the direction of interest were successfully converted. According to the obtained experimental results, the authors recommended analytical models for the LDSS fabricated square sections and proposed new models for the H-sections, through which the residual stress distributions for welded LDSS sections can be accurately predicted. In addition, the recommended/proposed analytical models for LDSS sections were further compared with their counterparts previously developed for high-strength steel (HSS) and ultra-high-strength steel (UHSS) welded sections. Graphical abstract: Unlabelled Image Highlights: Residual stresses of square and H-sections fabricated from LDSS plates were measured through neutron diffraction method. Hardness tests were conducted to ensure the welding quality and to facilitate the identification of weld region. Optical microscopy and EBSD methods were used to quantify the volume fraction of ferrite and austenite phase. The total residual stress of LDSS welded sections were calculated from the individual phase residual stresses. Design models for LDSS welded square and H-sections were recommended and proposed.